Capability of Print Media and Electronic Media in Analyzing News - Qorib, Ahmad; Saragih, M. Yoserizal (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
The scope of journalistic space usually revolves around journalistic work, news, and clarification of issues that are currently hot. The scope of this journalism applies not only in mass media, but also in electronic media such as radio and television broadcasts. Characters and its peculiarities include the aspects of the publishing philosophy, the technical dynamics of preparation and management, and the assumptions of the impact on the audience, listeners, or viewers. This chapter discusses some key aspects relating to journalism, namely the notion of journalism, at a glance the development of journalism, forms of journalism, journalistic products. The aim of this research is the activity of preparing, seeking, collecting, processing, presenting, and disseminating news through the media periodically to the widest possible audience. The research method is qualitative research.